2017
DOI: 10.1021/acs.orglett.7b00504
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Cross-Coupling of N-Sulfonylaziridines and Alkenylboronic Acids: Stereospecific Synthesis of Homoallylic Amines with Di- and Trisubstituted Alkenes

Abstract: A palladium-catalyzed cross-coupling of 2-alkylaziridines with alkenylboronic acids to give homoallylamines is presented. The reaction is highly regioselective and stereospecific and provides convenient access to enantioenriched amines with 1,1-disubstituted, 1,2-disubstituted, and trisubstituted alkenes. The modular synthesis of a 2,5-disubstituted pyrrolidine natural product was completed in three steps and 67% overall yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Aziridines have been employed successfully as C­(sp 3 ) electrophiles in a number of cross-coupling reactions. Work from our lab and those of Michael, Jamison, Takeda/Minakata, May, and Xiao have demonstrated that coupling reactions with aziridines can afford access to substituted ethylamines, important nitrogen-containing motifs in medicinal chemistry (Figure B) . Organometallic nucleophiles such as organozinc halides or organoboron reagents have been employed as coupling partners to form both C­(sp 3 )–C­(sp 2 ) and C­(sp 3 )–C­(sp 3 ) bonds (Figure B, top).…”
Section: Introductionmentioning
confidence: 97%
“…Aziridines have been employed successfully as C­(sp 3 ) electrophiles in a number of cross-coupling reactions. Work from our lab and those of Michael, Jamison, Takeda/Minakata, May, and Xiao have demonstrated that coupling reactions with aziridines can afford access to substituted ethylamines, important nitrogen-containing motifs in medicinal chemistry (Figure B) . Organometallic nucleophiles such as organozinc halides or organoboron reagents have been employed as coupling partners to form both C­(sp 3 )–C­(sp 2 ) and C­(sp 3 )–C­(sp 3 ) bonds (Figure B, top).…”
Section: Introductionmentioning
confidence: 97%
“…In particular Kauffmann and co-workers have prepared homoallylic amines by allylation of 2-azaallyl anions using allyl bromide as an electrophile 34 . Homoallylic amines are incredibly useful precursors for the synthesis of a vast number of biologically active molecules 11,[35][36][37][38][39][40][41][42][43][44][45][46][47][48] . Economical methods to prepare homoallylic amines remain in demand.…”
mentioning
confidence: 99%
“…Similar reaction conditions are applicable to the C3-selective ring-opening alkenylation of 2-alkylaziridines, which enables the syntheses of homoallylic amines (Scheme 12). 39 It is noted that the coupled products serve as useful synthetic precursors for 2,5dialkylpyrrolidines through acid-mediated diastereoselective intramolecular hydroamination across the CC bonds.…”
Section: C3-selective Ring-opening Arylation and Alkenylation Of 2-al...mentioning
confidence: 99%